Knockdown of miR‐423‐5p simultaneously upgrades the eNOS and VEGFa pathways in ADSCs and improves erectile function in diabetic rats. Issue 20 (20th September 2021) - Zhou, Jun; Yin, Yinghao; Yang, Yuan; Peng, Dongyi; Wei, Jingchao; Yin, Guangming; Tang, Yuxin
Abstract: This study aimed to explore the possibility of miR‐423‐5p modified adipose‐derived stem cell (ADSCs) therapy on streptozotocin (STZ)‐induced diabetes mellitus erectile dysfunction (DMED) rats. MiR‐423‐5p was knocked down in ADSCs. ADSCs, NC‐miR‐ADSCs and miR‐ADSCs were co‐cultured with human umbilical vein endothelial cells (HUVECs). Normal and high glucose media were supplemented. The supernatant and HUVECs were collected for assessment of eNOS and VEGFa expression, cell proliferation, and apoptosis. HUVECs co‐cultured with ADSCs or miR‐ADSCs exhibited higher eNOS and VEGFa protein expression levels compared to DM groups. MiR‐ADSCs enhanced HUVEC proliferation compared to the ADSCs and NC‐miR‐ADSCs. Lower apoptotic rates were observed when HUVECs were co‐cultured with miR‐ADSCs, compared to ADSCs and NC‐miR‐ADSCs. Fifteen male Sprague‐Dawley (SD) rats aged 12 weeks were induced to develop diabetes mellitus by intraperitoneal injection with STZ, and five healthy SD rats were used as normal controls. Eight weeks after developing diabetes, the rats received ADSCs and miR‐ADSCs via injection into the corpora cavernosa, whereas normal controls and DM controls were injected with saline. Erectile function and histological assessment of penile tissues were performed 8 weeks after injection. The ICP/MAP indicated that erectile function was impaired in the DM rats compared with the normal group. Injection of ADSCs and miR‐ADSCs improved erectile function significantly and was associated with the overexpression of eNOS and VEGFa. MiR‐423‐5p knockdown in ADSCs ameliorated high glucose‐mediated damage to HUVECs and improved erectile function in DM rats by inducing eNOS and VEGFa overexpression, indicating that miR‐423‐5p may be a potential target in the treatment of DMED.